2020
DOI: 10.1101/2020.01.06.895920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide comparison of DNA methylation between life cycle stages ofDrosophila melanogasterusing high-throughput sequencing techniques

Abstract: 28Drosophila melanogaster undergoes holometabolous development, has very low levels of 29 DNA methylation, and is known to possess a single known methyltransferase, dDNMT2. 30 This study compares the DNA methylation patterns between the two life cycle stages of D. 31 melanogaster using a combination of DNA immunoprecipitation and high throughput 32 sequencing techniques. 33 Our results indicate, a change in the chromosomal distribution of the sparse DNA 34 methylation concerning genes and natural t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Subsequently, the samples were also homogenized with an ultrasonic homogenizer (SONOPULS UW 2070, BANDELIN electronic GmbH&Co. KG) two times for 10 s on ice. 45 µL of sample was mixed with 50 µL of 10% trichloroacetic acid and 5 µL of 100 µM labelled internal standard solution (L-Ascorbic Acid- 13 C 6 ,Toronto Research Chemicals) and incubated for 20 min. Then, the samples were vortexed and centrifuged at 24 400x g for 20 min at 4 ℃.…”
Section: Determination Of Intracellular Concentrations Of Ascorbate I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the samples were also homogenized with an ultrasonic homogenizer (SONOPULS UW 2070, BANDELIN electronic GmbH&Co. KG) two times for 10 s on ice. 45 µL of sample was mixed with 50 µL of 10% trichloroacetic acid and 5 µL of 100 µM labelled internal standard solution (L-Ascorbic Acid- 13 C 6 ,Toronto Research Chemicals) and incubated for 20 min. Then, the samples were vortexed and centrifuged at 24 400x g for 20 min at 4 ℃.…”
Section: Determination Of Intracellular Concentrations Of Ascorbate I...mentioning
confidence: 99%
“…They show the de novo DNA methyltransferase activity in adult D. melanogaster and the presence of CpC methylation in selected genomic regions 12 . Deshmukh et al observed the presence of methylation in ies with a dDNMT2 knockout, although the methylation pro le was altered 13 . Methylation is also observed in the RNA of many species.…”
Section: Introductionmentioning
confidence: 99%
“…These authors showed de novo DNA methyltransferase activity in adult D. melanogaster and the presence of CpC methylation in selected genomic regions 12 . Deshmukh et al observed the presence of methylation in flies with a dDNMT2 knockout, although the methylation profile was altered 13 .…”
mentioning
confidence: 99%